Changes in the content of interleukins in the serum of male and female rates with different resistance to acute hypoxic hypoxia under immobilization stress - O. V. Denefil; Iu. M. Ordynskyi (Kazimierz Wielki University, 2020)
Attention of scientists of the world are study the features of increased resistance to hypoxia and stress, different development inflammation in them. The aim of the study was to trace the features of interleukins level in high- and low-resistance to hypoxic hypoxia rats (HR, LR) in different models of immobilization stress. Material and methods of investigation. The experiments were performed on 144 outbred HR and LR aged 5.5-6 months, dividing into 3 groups - control and 2 with different model of immobilizing stress. Determine concentration of interleukins 1beta, 2, 4, 6, 10 (IL-1beta, IL-2, IL-4, IL-6, IL-10), tumor necrosis factor alpha (TNF-alpha) in the blood serum. Results. High congenital resistance to hypoxia is associated with an increased content of anti-inflammatory cytokines (in males - IL-4 on 24.73% (p<0.001), in females - IL-10 on 37.36%; p<0.001). Intact males, compared with females, have a higher production of pro-inflammatory cytokines (IL-6, TNF-alpha). Intact males, compared with females, are dominated by the content of pro-inflammatory cytokines in the blood. In HR males, compared with females, a higher content of IL-6 (49.93%; p<0.01), TNF-alpha (10.85%; p<0.01), IL-4 (33.92%; p<0.001), lower - IL-1beta (37.91%; p<0.02) and IL-10 (93.06%; p<0.001). In LR males, compared with females, higher blood levels of IL-1beta (42.98%; p<0.001), IL-6 (54.32%; p<0.001), TNF-alpha (16,40%; p<0,002), the highest level of pro-inflammatory cytokines under stress with a frequency of every 24 hours. In HR males under these conditions, the level of IL-1beta increases (in 2.35 times; p<0.001), TNF-alpha (in 8.20 times; p<0.001). In exposed to stress every 72 hours in HR males, the level of TNF-alpha increases in 2.88 times (p<0.002), and in LR males in 5.18 times (p<0.001). At the same time, in HR females its level increases in 3.25 times (p<0.01), in LR females - in 5.73 times (p<0.01). Conclusion. The experiments revealed the changes of pro- and anti-inflammatory interleukins, which depends of sex, resistance to hypoxy and kinds of stress.